Quality Improvement and Wastage Costs Reduction in Warehouses of a Structural Business in Pathum Thani Province - Chaveewong, Artittaya; ทองเรือนดี นพัชกร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research focuses on the study of quality improvement and cost reduction of losses in the warehouse of a structural work business located in Pathum Thani Province. It is a qualitative research study that emphasizes the importance of enhancing quality and minimizing cost losses. The objectives of the study are: (1) to examine the workflow process and explore methods for reducing unnecessary steps, as well as improving and correcting processes to achieve maximum efficiency, and (2) to study and develop solutions to the identified problems by applying the PDCA quality management cycle. Techniques such as the Flow Process Chart, Fishbone Diagram, and PDCA were utilized in this research. Data were collected through unstructured and informal interviews, observation of actual workflow processes, and historical data from the year 2024. From the application of the Flow Process Chart to analyze the original workflow, it was found that the existing process was inefficient, taking a total of 109 minutes to complete. The inefficiencies stemmed from 103 misplaced items, 26 damaged items, insufficient storage space, and 19 expired items. After applying the Fishbone Diagram to analyze root causes and implementing improvements through the PDCA cycle, the results showed a 64.08% reduction in misplaced items, an 80.77% decrease in damaged items, sufficient storage space availability, elimination of expired items in the warehouse, and a reduction in workflow time to 60 minutes, representing a 44.95% decrease